Alterações funcionais e histológicas das glândulas paratireóides após derivação jejuno-cólica: estudo comparativo em ratos - Carreiro, Mario Castro (1997)
To study the parathyroid glands during the weigth reduction phase, 48 male Wistar rats were divided into two groups. The animals in group one, totaling 28, were submitted to jujunocolic shunts (JCS). The animals in group two, were submitted to sham operations. The histological aspects were study by optical and electronic microscopy. Parathyroid gland function was tested by serial determination of serum parathyroid hormone (PTH) level, and serum calcium, phosphate, albumin and total protein. The evolutionevaluations was carried out by weighing the animal on days 0, 7, 14, 21 and 28. Serial determinations of PTH, calcium, phosphate, albumin and total protein levels were carried out prior to sacrificing the animals. The hystological studies were done after thet on days 7, 14, 21 and 28 respectively, depending on witch day the animal was submitted to JCS. The values for weights and their percentage deviations as well as the biochemical and hormonal determinations were sumitted to separate statistical analyses for each group. Group aon and two were also compared relative to the variables studied on each of the periods of sacrifice. The animals given JCS presented with progressive weight loss beginning on day 7 foward. The control animals demonstrated increasing weight gain starting on day 14. The avarage values of PTH in the rats given JCS were greater than those of control animals starting on the 7th day , although the p values were not statistically signification . P values for the serial phosphate values were statistically signification only on the 21st and the albumin values on days 14, 21 and 28. The values for serum toral proteins were statistically significant during the whole study period. The average values of calcium were smaller in the control group given JCS, although the difference was not statistically significant. The histologic findings of both groups were compared under light and electronic microscopy. The major distinction between their respective histological aspects consisted in the predominance of the dark and light principal cells in the operated group. The predominance of the dark cells occurred on the 21st day and the light cells occurred on the 28 day.